New insights into inflammatory memory of epidermal stem cells - Cheng, Dapeng; Zhu, Xiaochen; Yan, Shaochen; Shi, Linli; Liu, Zhi; Zhou, Xin; Bi, Xinling (Frontiers in Immunology, 2023)
Inflammatory memory, as one form of innate immune memory, has a wide range of manifestations, and its occurrence is related to cell epigenetic modification or metabolic transformation. When re-encountering similar stimuli, executing cells with inflammatory memory function show enhanced or tolerated inflammatory response. Studies have identified that not only hematopoietic stem cells and fibroblasts have immune memory effects, but also stem cells from various barrier epithelial tissues generate and maintain inflammatory memory. Epidermal stem cells, especially hair follicle stem cells, play an essential role in wound healing, immune-related inflammatory skin diseases, and skin cancer development. In recent years, it has been found that epidermal stem cells from hair follicle can remember the inflammatory response and implement a more rapid response to subsequent stimuli. This review updates the advances of inflammatory memory and focuses on its mechanisms in epidermal stem cells. We are finally looking forward to further research on inflammatory memory, which will allow for the development of precise strategies to manipulate host responses to infection, injury, and inflammatory skin disease.